2017
DOI: 10.5935/0103-507x.20170054
|View full text |Cite
|
Sign up to set email alerts
|

Dysglycemia in the critically ill patient: current evidence and future perspectives

Abstract: Dysglycemia in critically ill patients (hyperglycemia, hypoglycemia, glycemic variability and time in range) is a biomarker of disease severity and is associated with higher mortality. However, this impact appears to be weakened in patients with previous diabetes mellitus, particularly in those with poor premorbid glycemic control; this phenomenon has been called "diabetes paradox". This phenomenon determines that glycated hemoglobin (HbA1c) values should be considered in choosing glycemic control protocols on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0
3

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 60 publications
0
16
0
3
Order By: Relevance
“…According to international recommendations, blood glucose levels should be maintained at 140-180 mg/dL for normoglycaemic patients and 180-200 mg/dL for previously diabetic individuals. 20 Both the hypoand hyperglycaemic effects of AlP are attributable to the wide variety of changes in magnesium, calcium, phosphate, citrate and cortisol levels that result from AlP poisoning. 11,21 These biochemical changes can act as either stimulatory or inhibitory modulators of the enzymes and hormones that catalyse and regulate the metabolism of glucose.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to international recommendations, blood glucose levels should be maintained at 140-180 mg/dL for normoglycaemic patients and 180-200 mg/dL for previously diabetic individuals. 20 Both the hypoand hyperglycaemic effects of AlP are attributable to the wide variety of changes in magnesium, calcium, phosphate, citrate and cortisol levels that result from AlP poisoning. 11,21 These biochemical changes can act as either stimulatory or inhibitory modulators of the enzymes and hormones that catalyse and regulate the metabolism of glucose.…”
Section: Discussionmentioning
confidence: 99%
“…23 Among critically-ill patients, blood glucose alterations have been associated with prolonged hospital stays as well as increased mortality. 20,24 However, to the best of the authors' knowledge, only one previous study has examined the relationship between hyperglycaemia and AlP poisoning outcomes. Mehrpour et al published a prospective study of 45 patients with acute AlP poisoning, of which 32 patients (71%) died.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, more attention has been paid to the study of blood glucose variability (GV) on disease progression and prognosis of patients, and it has important clinical signi cance for monitoring and controlling of blood GV in severe patients 9,10 . Compared with hyperglycemia, blood GV better re ects changes in the condition and has greater adverse effects on the body, which may have higher clinical value 10,11 . It is well known that blood GV increases the risk of adverse events after cardiac surgery, such as acute kidney injury, and the risk of short-term and long-term death 12,13 .…”
Section: Introductionmentioning
confidence: 99%
“…In the critically ill adult, dysglycemia is a marker of disease severity and is associated with worse clinical outcomes. 1 The common practice of close monitoring of glucose in critical illness and management using insulin finds its roots in the seminal randomized study by van den Berghe and colleagues in 2001 2 which showed a 42% decrease in mortality with tight glucose control (TGC; 80-110 mg/dL) in patients who remained in the surgical critical care unit for a period over 5 days. However, a similar trial by the authors in the medical intensive care unit (ICU) did not replicate the same mortality benefit.…”
mentioning
confidence: 99%